Anatomy : 1800 multiple choice questions - Fitzgerald, M. J. T. (Butterworths, 1986)
Anatomy: 1800 Multiple Choice Questions contains 1,800 multiple choice questions related to anatomy. The questions are supported by illustrations and arranged into nine sections: Upper Limb, Lower Limb, Thorax, Abdomen, Pelvis and Perineum, Head and Neck, Nervous System, Histology, and Embryology. In the Histology section, the questions in each of the six standard formats are arranged in the same sequence, as follows: the Cell; the Tissues (commencing with the Epithelia and ending with Nervous Tissue); and the Systems (commencing with the Cardiovascular and ending with the Reproductive). Reade.